Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(dy=d\left(\dfrac{\sqrt{x}}{a+b}\right)=\left(\dfrac{\sqrt{x}}{a+b}\right)dx=\dfrac{1}{2\left(a+b\right)\sqrt{x}}dx\)
b) \(dy=d\left(x^2+4x+1\right)\left(x^2-\sqrt{x}\right)=\left[\left(2x+4\right)\left(x^2-\sqrt{x}\right)+\left(x^2+4x+1\right)\left(2x-\dfrac{1}{2\sqrt{x}}\right)\right]dx\)
y'=\(\dfrac{1}{cos^2x}-\dfrac{1}{cos^2x}tan^2x+\dfrac{1}{cos^2x}tan^4x\)
=\(\dfrac{1}{cos^2x}-\dfrac{sin^2x}{\cos^4x}+\dfrac{\sin^4x}{\cos^8x}\)
=\(\dfrac{\cos^4x-\sin^2.\cos^2x+\sin^4x}{\cos^8x}\)
=\(\dfrac{\left(\cos^2x+\sin^2x\right)^2-3\sin^2x\cos^2x}{\cos^8x}\)
=\(\dfrac{-3\sin^2x}{\cos^6x}\)
Lời giải:
a) y' = = , y" = = = .
b) y' = = ;
y" = = = .
c) y' = ; y" = = = .
d) y' = 2cosx.(cosx)' = 2cosx.(-sinx) = - 2sinx.cosx = -sin2x,
y" = -(2x)'.cos2x = -2cos2x.
a)\(\forall x\Rightarrow sinx\le1\Rightarrow1-sinx\ge0\)
cosx\(\ge-1\Rightarrow1+cosx\ge0\)
ĐK:cosx\(\ne-1\Leftrightarrow x\ne\pi+k2\pi\)
\(\Rightarrow D=\left\{R\backslash\left\{\pi+k2\pi\right\}\right\}\)
b)ĐK:\(cos\left(2x+\frac{\pi}{3}\right)\ne0\Leftrightarrow2x+\frac{\pi}{3}\ne\frac{\pi}{2}+k\pi\Leftrightarrow x\ne\frac{\pi}{12}+\frac{k\pi}{2}\)
\(\Rightarrow D=\left\{R\text{\}\left\{\frac{\pi}{12}+\frac{k\pi}{2}\right\}\right\}\)